Effect of Age and Sex on the Growth and Carcass Characteristics of Giriraja Birds and Selection of Ideal Slaughter Age - Kogilasan, D; Mandal, P K; Venugopal, S; Pal, U K; Kasthuri, S; Gawdaman, G (Journal of Meat Science, 2026)
An experiment was conducted with the aim to examine the effect of age and sex on growth and slaughter characteristics of Giriraja birds to find the ideal age of slaughter. A total of 100 day old Giriraja chicks were procured and divided into two groups viz., male (47 birds) and female (53 birds) after completion of 6 weeks of age. Growth and feed consumption was recorded till 12th week. Six birds each from male and female were slaughtered every week from 8 to 12 weeks as per the standard procedures and all the slaughter and carcass data were collected. In male and female Giriraja birds, the highest weekly body weight gain was recorded in 11th and 5th weeks, respectively, which were significantly (P<0.01) higher than other weeks. The cumulative FCR at 8 weeks of age was found to be economically better. In Giriraja birds, highly significant (P<0.01) differences were recorded in pre-slaughter weight (PSW) of the birds belonging to different weeks of age. There were no significant differences (P>0.05) in yield of blood, feather, head and shank, abdominal fat, giblets, and dressing percentage in male birds belonging to different weeks of age for both male. In case of female significant differences (P<0.05) were recorded in head and shank, giblets and dressing percentage at different weeks of age. In male birds age of slaughter had a significant (P<0.05) effect in the yield of back and neck percentage, whereas, in female age of slaughter had a significant (P<0.05) effect only in the yield of breast. The PSW and dressed weight of male birds were significantly (P<0.01) higher than female birds. From this study, it was concluded that age and sex of Giriraja bird has remarkable effect on the growth and carcass characteristics. Based on the growth, carcass characteristics, 8 weeks of age was found to be optimum for slaughter of Giriraja birds.